Arequipa and the Southern Andean Region: Trade and Supply in the Agony of the Colonial Regime - Condori, Víctor (2025)
The present research work seeks to approach the political, military and economic situation that was experienced in the Intendancy of Arequipa throughout 1824, the last year of the war of the independence; likewise, highlight the relationship of said capital with some regions located to the south of the Peruvian viceroyalty and, in this way, be able to explain the impact generated by the aforementioned war conflict, both on commercial activities and on the food supply channels, struc-tured since several decades around the Arequipeñan urbe and very closely related to the South Andean provinces of Cusco, Puno and La Paz. All this, on the eve of the arrival of the first republican authority of the department, appointed im-mediately after the defeat of the royalist army in the battle of Ayacucho.